Nursing Performance in the Care of Gestational Diabetes: An Integrative Literature Review - Nedson Sombra Gemaque; Mauricio Henrique Pontes Santos; Marcela dos Santos Bastos Costa; Mauricio Guilherme Nunes Ribeiro; Marielly Brandão dos Santos; Clerislene de Sousa Oliveira; Adrya Karolinne da Silva Martin; Elaine Cristina Pereira Monteiro; Alcirene Viana Corrêa (Archives of Current Research International, 2025)
Background: gestational Diabetes Mellitus (GDM) is a condition characterized by glucose intolerance with onset or first recognition during pregnancy. It poses significant risks for both maternal and fetal health, including preeclampsia, macrosomia, and neonatal hypoglycemia. The increasing prevalence of GDM highlights the need for comprehensive prenatal care, in which nursing professionals play a pivotal role. Objective: to analyze the role of nursing professionals in the care of pregnant women with Gestational Diabetes Mellitus (GDM), highlighting the importance of humanized care, diagnosis and treatment. Methods: integrative literature review with the selection of five articles after analyzing 18,610 found on platforms such as SciELO, Portal CAPES, and Google Scholar. Results: the importance of humanizing nursing care, glycemic monitoring, health education, and psychological support was observed. The implementation of care protocols based on scientific evidence, together with the continuing education of nursing professionals, is essential to optimize treatment and prevent complications. Conclusion: the role of nurses is essential to promote the quality of life of pregnant women and their babies, ensuring effective control of GDM.